ENHANCING SECONDARY-LEVEL STUDENTS’ WRITING MOTIVATION USING CHATGPT AS A WRITING ASSISTANT - Sinta Nurul Holifah; Dyah Ayu Nugraheni; Fatih Al-Fauzi (JR-ELT (Journal of Research in English Language Teaching), 2025)
Writing has long been recognized as one of the most challenging skills for secondary-level EFL learners. This study explored how ChatGPT, a widely used artificial intelligence tool, can support students’ writing development, especially in terms of motivation, confidence, and participation. Conducted through Classroom Action Research with a single cycle, the study involved 24 ninth-grade students at SMP Al-Miftah Silo. The data were gathered through observations, students’ writing samples, and a motivation questionnaire administered before and after the intervention. The results indicate that the integration of ChatGPT helped students become more confident in generating ideas, more willing to revise their writing, and more engaged during lessons. Motivation increased from 35% to 70%, participation rose from 30% to 80%, and grammatical accuracy improved with a 60% reduction in errors. These findings suggest that ChatGPT, when used under teacher guidance, offers meaningful support for young EFL learners and encourages a more positive writing atmosphere.